Full Employment, as the Hearth of the Cultural Economics of Orban. Issue 3 (4th May 2021) - Skidelsky, Robert; Olah, Daniel
Abstract: The authors take a novel look at recent Hungarian economic policy achievements of Orban governments. Compared to the Hungarian economic policies of the 2000s and the decades after 1989 up to 2010, Orbanomics is a successful macroeconomic and social development strategy. Its measures are not simply improvisatory elements, but constitute a new framework of policymaking, what we call culturally embedded economic policymaking. Its political pedigree and context is briefly outlined. The past 10 years of Orbanomics provides an underresearched policy laboratory, in which the application of a wide-scale job guarantee program or a growth-friendly, inclusive stabilization building on the balanced budget multiplier can be studied.